Translatologia z perspektywy końca (wieku) - Legeżyńska, Anna (Przestrzenie Teorii, 2007)
When summing up the history of translatology in the second half of the 20th century, the author points to undoubtful achievements of this discipline as well as disputable questions and tasks for the future. She proves that the postmodern conceptions of the exhaustion of literature (Lyotard) are not reflected in studies of translation. Just the opposite, this field has been developing dynamically, although its autonomy is still questioned. The chance of translatology is its interdisciplinary character, relation with methodology of linguistic studies, using the theory of interpretation and the theory of intertextuality. Some of the questions which are disputed are: equivalentisation, non-translatability, opposition of archaisation and modernisation. In the sphere of postulates is the synthesis of Polish knowledge on translation, Formation of proper criticism of translation and codification of terminology. All these motifs of considerations are supported by references to the most important conceptions and trends of the 20th century translatology.